2021
DOI: 10.1186/s12969-021-00605-2
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for canakinumab initiation among patients with periodic fever syndromes: a retrospective medical chart review from the United States

Abstract: Background Although canakinumab has demonstrated efficacy in multiple trials in patients with periodic fever syndromes (PFS), the evidence on initiation of canakinumab among PFS patients in real world setting is not well understood. We aimed to characterize the reasons for canakinumab initiation among patients with PFS, specifically, cryopyrin-associated periodic syndrome (CAPS), hyperimmunoglobulin D syndrome/mevalonate kinase deficiency (HIDS/MKD), TNF receptor-associated periodic syndrome (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Participating physicians included those who had prescribed canakinumab to ≥ 1 patient with Still’s disease from 2016 to 2018 and agreed to extract patient data in an online case report form (CRF). The methods are described in detail elsewhere [ 15 ].…”
Section: Methodsmentioning
confidence: 67%
“…Participating physicians included those who had prescribed canakinumab to ≥ 1 patient with Still’s disease from 2016 to 2018 and agreed to extract patient data in an online case report form (CRF). The methods are described in detail elsewhere [ 15 ].…”
Section: Methodsmentioning
confidence: 67%
“…in MKD is the basis for the use of canakinumab in this condition, with the aim of limiting all the IL-1β-related clinical manifestations. 2,6 Some authors suggested that an impaired prenylation of RhoA protein could be responsible for the IL-1β hypersecretion in MKD, through an increased activity of autoinflammatory pathways, as Rac1/PKB signaling and inflammasome-mediated routes. 8 Canakinumab was administered at a regular dosage (2 mg/kg every 4 weeks for patients <40 kg, 150 mg every 4 weeks for patients >40 kg).…”
Section: The Evidence Of Excessive Production Of Interleukin-1β (Il-1β)mentioning
confidence: 99%
“…2 Therefore, biological drugs are often needed to control inflammation after the failure of conventional treatments. 2 Anti-interleukin 1 (IL-1) drugs are approved for the treatment of PFS with a favorable safety and tolerability. 2,3 The 2021 EULAR/American College of Rheumatology recommendations state that in children with MKD, an anti-IL1 therapy is generally required.…”
mentioning
confidence: 99%
See 2 more Smart Citations